Development of Land Suitability Assessment Applications for Sorghum, Sweet Potato and Sugarcane - Rahim, Supli; Muchsiri, Mukhtarudin; Supli, Ahmad Affandi; Damiri, Nurhayati; Supli, Nur Aslamiah; Aminah, Iin Siti; Djazuli, Abid; Rosmiah, Rosmiah (Indonesian Soil Science Society of South Sumatra in Collaboration With Soil Science Department, Sriwijaya University, 2024)
Cultivation of food crops should be done on suitable land based on the results of the soil suitability assessment. The Soil Suitability Assessment Framework was initiated by the Food and Agriculture Organization (FAO). Today, smartphones have become a ubiquitous technology for solving problems in most environments, including: Assessment of soil suitability for food crops, plantations and many others. This white paper aims to address these benefits by transforming the framework into a mobile app. This solution aims to help land users conduct land valuations more effectively and efficiently. A rule-based system (RBS) algorithm is used to build the framework into a set of rules that are interconnected to draw land suitability conclusions. Regulations relate to annual rainfall, land topography, drainage, soil type, pH, flood risk, soil fertility, soil depth, etc. Only three of his food crops, sorghum, sweet potato, and sugarcane, will be evaluated in this study. Agroclimatic data governing crop suitability have evolved into generic and crop-specific criteria. An application that assesses land suitability for three food crops will be available on the Play Store for smartphones. Usability models were surveyed by 35 respondents who used the app. The user-friendliness of the app was evaluated as